Relationship between parenting styles, personality traits and academic procrastination among undergraduates - Yusoff, Nur Shuhada; Salim, Siti Suria (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Academic procrastination has been a common and widespread problem among students in university. This study aims to determine the relationship between parenting styles and personality traits with respect to academic procrastination among undergraduates. The concept paper looks at the rational of studying academic procrastination, problem statements and its significance as well as past studies highlighting the variables involved.